Analisis Perubahan Sosial dan Pembangunan di MTs YPAK Cigugur: Tinjauan Terhadap Peran Lembaga Pendidikan dalam Transformasi Sosial Masyarakat - Dede Mulyana; Galang Pratama Sudiar; Hilmy Farhani Ali (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The rapid development of the times has brought about significant changes in various aspects of human life. From day to day, week to week, there are constant changes happening to individuals, groups, and societies. Social changes that occur in society encompass economic, cultural, political, and educational aspects. These changes do not always lead to improvement but can also move in the opposite direction. An analysis of Social Change and Development at MTs YPAK Cigugur: A Review of the Role of Educational Institutions in Social Transformation aims to prepare human resources, such as the community, to face these changes. The purpose of writing this article is to study the data collection technique, which was conducted through direct interviews with sources and literature studies. The research results discuss the changes in students' social behavior at MTs YPAK Cigugur due to the use of smartphones. The use of social media among MTS students, especially in the ninth grade at MTs YPAK Cigugur, influences changes in students' social behavior, particularly within the school environment. Therefore, appropriate supervision by teachers and parents is necessary regarding students' smartphone usage. With good supervision, it is hoped that the negative impact of social media usage can be minimized, and students can use social media positively to support their learning and social development.